2006
DOI: 10.1165/rcmb.2005-0339oc
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Nitrogen Species Augment Fibroblast-Mediated Collagen Gel Contraction, Mediator Production, and Chemotaxis

Abstract: Reactive nitrogen species (RNS) such as peroxynitrite cause cellular injury and tissue inflammation. Excessive production of nitrotyrosine, which is a footprint of RNS, has been observed in the airways of patients with asthma and chronic obstructive pulmonary disease, disorders characterized by tissue remodeling. The aim of this study was to evaluate whether RNS can affect tissue remodeling through direct effects on fibroblasts, and to determine if these effects depend on production of transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Recently, we have shown that peroxynitrite, one of the RNS, stimulates fibroblasts. Peroxynitrite stimulates the differentiation of fibroblasts into myofibroblasts and extracellular matrix protein production in vitro [23,30], suggesting that RNS induce fibroblast-mediated profibrotic responses. In the current study, free 3-nitrotyrosine caused the inhibition of tissue remodelling in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have shown that peroxynitrite, one of the RNS, stimulates fibroblasts. Peroxynitrite stimulates the differentiation of fibroblasts into myofibroblasts and extracellular matrix protein production in vitro [23,30], suggesting that RNS induce fibroblast-mediated profibrotic responses. In the current study, free 3-nitrotyrosine caused the inhibition of tissue remodelling in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen gels were prepared as described previously [22,23]. Briefly, RTTC, distilled water and 46 concentrated DMEM were combined so that the final mixture resulted in 0.75 mg?mL -1 collagen, with a physiological ionic strength of 16 DMEM and a pH of 7.4.…”
Section: Collagen Gel Contraction Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline expression of XOR is low; however, transcription can be up-regulated due to several factors, such as hypoxia, lipopolysaccharide (LPS), IFN-γ, IL-1, IL-6, tumor necrosis factor-α (TNF-α), and steroid stimulation. XOR activation is increased in the late allergic response phase (37).…”
Section: Endogenous Oxidants and Allergic Asthmamentioning
confidence: 99%